ENZYMOSOMES: A RISING EFFECTUAL TOOL FOR TARGETED DRUG DELIVERY SYSTEM - S., Shefrin; S., Sreelaxmi C.; Vijayan, Vishnu; Nair, Sreeja C. (International Journal of Applied Pharmaceutics, 2017)
The study aims to develop enzymosomes as an emerging novel drug delivery system for site-specific action. Enzymosomes utilises the specific nature of an enzyme, which is binding to a specific substrate at a controlled rate and catalysing product production step. An enzyme is encapsulated by coupling covalently to the surface of liposomes/lipid vesicles to form enzymosomes. Enzymes links through acylation, direct conjugation, physical adsorption, encapsulation methods to prepare enzymosomes with targeted action. Such novel drug delivery systems prove effective drug release and concomitantly reduces undesirable side effects of conventional treatment methods and hence showcase improvement in the long-term therapy of the disease. They are a promising substitute to conventional treatment therapies of gout, antiplatelet activities etc. Enzymosomes are newly designed supramolecular vesicular delivery systems to be useful as a tool in pharmaceutics for the raising of drug targeting and physicochemical properties and hence bioavailability. It shows beneficial effects of drugs with a narrow precision because targeting of these drugs to their site of action improves the drugs overall pharmacodynamics and pharmacokinetic profile. It also minimizes alterations in the normal enzymatic activity, thus enhancing half-life and achieve enzyme activity on targeted sites such as cancerous cells.